2011
DOI: 10.1007/s00284-011-9868-6
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-resistance Transferability from VanA Enterococci to Staphylococcus aureus

Abstract: In last decade methicillin-resistant Staphylococcus aureus with high level of vancomycin-resistance (VRSA) have been reported and generally the patients with VRSA infection were also infected with a vancomycin-resistant Enterococcus (VRE). Considering that the high level of vancomycin-resistance in VRSA isolates seems to involve the horizontal transfer of Tn1546 transposon containing vanA gene from coinfecting VRE strains, the authors have studied the "in vitro" conjugative transfer of this resistance from Van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 16 publications
0
62
0
4
Order By: Relevance
“…Vancomycin is one of the few antibiotics that can be used to treat infections resulting from Gram-positive multidrug-resistant organisms (MDRO), such as MRSA; therefore, transmission of vancomycin resistance from enterococci to MRSA is of major concern. Horizontal gene transfer has been shown to be a mechanism of transmission between enterococci, and in vitro studies have demonstrated that transfer between Enterococcus and S. aureus can occur (33). In 2002, the first case of vancomycin-resistant S. aureus (VRSA) was isolated from a 40-year-old diabetic patient undergoing dialysis and was obtained from a dialysis catheter cultured from both the exit site and catheter tip.…”
Section: Antimicrobial Resistance Mechanisms and Approaches To Therapymentioning
confidence: 99%
“…Vancomycin is one of the few antibiotics that can be used to treat infections resulting from Gram-positive multidrug-resistant organisms (MDRO), such as MRSA; therefore, transmission of vancomycin resistance from enterococci to MRSA is of major concern. Horizontal gene transfer has been shown to be a mechanism of transmission between enterococci, and in vitro studies have demonstrated that transfer between Enterococcus and S. aureus can occur (33). In 2002, the first case of vancomycin-resistant S. aureus (VRSA) was isolated from a 40-year-old diabetic patient undergoing dialysis and was obtained from a dialysis catheter cultured from both the exit site and catheter tip.…”
Section: Antimicrobial Resistance Mechanisms and Approaches To Therapymentioning
confidence: 99%
“…En cuanto a la tipificación del genotipo de resistencia, todas las cepas ERV que fueron aisladas, tenían el gen de resistencia a la vancomicina vanA. Este gen que confiere altos niveles de resistencia a la vancomicina codifica enzimas que modifican el sitio de acción de la vancomicina sobre la pared celular bacteriana e inhiben su efecto bactericida (2,10) . Asimismo, desde el primer reporte del Staphylococcus aureus vancomicino resistente (VRSA) en el 2002, diversos estudios in vitro y reporte de casos han demostrado que el gen vanA es también responsable de la resistencia a la vancomicina en la especie Staphylococcus aureus vancomicino resistente (VRSA).…”
Section: Discussionunclassified
“…En estos mismos estudios se ha confirmado la transmisibilidad del gen vanA mediante transposones, desde cepas de ERV a cepas de Staphylococcus aureus meticilino resistente (MRSA). Hasta el día de hoy se conoce que todas las cepas VRSA que han sido aisladas en pacientes de los Estados Unidos, provenían de cepas MRSA que adquirieron el gen vanA de cepas ERV que colonizaban al mismo paciente (2,8,(10)(11)(12)(13)(14)(15) . En cuanto al análisis bivariado de los factores asociados a la colonización, sólo las variables: hospitalización previa y el uso de cefalosporinas de tercera generación estuvieron asociadas.…”
Section: Discussionunclassified
See 2 more Smart Citations